2009
DOI: 10.1093/europace/eup173
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output response to changes of the atrioventricular delay in different body positions and during exercise in patients receiving cardiac resynchronization therapy

Abstract: AimsThe aim of this study was to study the haemodynamic effect of atrioventricular delay (AVD) modifications within a narrow range in different body positions and during exercise in patients receiving cardiac resynchronization therapy (CRT). MethodsThe previously optimized AVD was shortened and prolonged by 40 ms in 27 CRT patients and 9 controls without heart failure. Cardiac output (CO) was measured by inert gas rebreathing (Innocor) as the average over different body positions (left-lateral, supine, sitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…This shows that AV‐ and VV‐delay optimization leads to an increase in CO that is not only arbitrary but can be reproduced with a high concordance after a long period of time. From a methodical point of view, this confirms the reliability of the method in patients with HF, what has also be shown in a recently published paper investigating the acute hemodynamic response to different AV delays in CRT patients 28 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This shows that AV‐ and VV‐delay optimization leads to an increase in CO that is not only arbitrary but can be reproduced with a high concordance after a long period of time. From a methodical point of view, this confirms the reliability of the method in patients with HF, what has also be shown in a recently published paper investigating the acute hemodynamic response to different AV delays in CRT patients 28 …”
Section: Discussionsupporting
confidence: 83%
“…From a methodical point of view, this confirms the reliability of the method in patients with HF, what has also be shown in a recently published paper investigating the acute hemodynamic response to different AV delays in CRT patients. 28…”
Section: Acute Effects Of Cardiac Output Optimizationmentioning
confidence: 99%
“…5). Previous publications have examined the effect of programming AVDs 50 ms longer or shorter than the optimal value and have demonstrated that the short AV delays produce significantly inferior EF 7 and cardiac output 30 . In the present study 30 ms was chosen as the hemodynamically significant deviation from the optimal AVD.…”
Section: Discussionmentioning
confidence: 96%
“…Previous publications have examined the effect of programming AVDs 50 ms longer or shorter than the optimal value and have demonstrated that the short AV delays produce significantly inferior EF 7 and cardiac output. 30 In the present study 30 ms was chosen as the hemodynamically significant deviation from the optimal AVD. When compared with fixed programming of SAV = 100 ms or 120 ms and PAV = 130 or 150 ms, which are the nominal values for the majority of device manufacturers, ECG-based AVD delay adjustment could have halved the proportion of suboptimally programmed patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 215 patients, 9% patients showed improvement in ≥1 diastolic function stage after undergoing AV optimization (Ritter or iterative method) . Stahlberg et al ., by means of an indirect estimate of the LA end‐diastolic pressure—derived from the estimated pulmonary artery diastolic pressure obtained from a sensor in the RV outflow tract (Implantable Haemodynamic Monitor (IHM) Chronicle ® , Medtronic Inc., USA)—were able to show lower LA‐derived pressures following AV optimization (21.9 ± 8.1 mmHg vs. 23 ± 7.7 mmHg, respectively, P < 0.05) . Recently, using a novel direct continuous invasive ambulatory LA monitoring system (HeartPOD™ ISL St Jude Medical) the optimal AV delay (also using the transmitral iterative method) clearly correlated with a reduction in the LA pressures and improved LA filling profile …”
Section: Discussionmentioning
confidence: 99%